Oral Topical Doxepin Rinse: Anesthetic Effect in Normal Subjects - Joel B Epstein; Edmond L Truelove; Hal Oien; Nhu D Le; Mathew S Epstein (Pain Research and Management)
Oral doxepin rinse has been reported to provide pain relief in patients with oral mucosal lesions due to cancer or cancer therapy. The purpose of this study was to assess the anesthetic effect of doxepin oral rinse in normal subjects to identify the duration of effect and to contrast the anesthetic effect with reported pain relief in patients with oral mucosal lesions. Normal volunteers were provided a solution of doxepin (5 mg/mL) for oral rinsing. Oral numbness and adverse effects were recorded for a period of 4 h after rinsing. Doxepin rinse resulted in mucosal anesthesia in all subjects. Sedation/fatigue was reported in four of seven subjects. There were no taste complaints and no nausea reported. The limited duration of numbness/anesthesia in normal subjects compared with prior studies showing pain relief for more than 3 h in patients with mucosal lesions, suggests that the extended duration of pain relief in patients was due to analgesic effects rather than anesthetic effects. The majority of normal subjects reported sedation after use, but this was less common in patients with mucosal lesions.